A fuzzy MCDM and simulation approach for traffic flow enhancement - Magableh, Ghazi M.; Sobeih, Ghadeer A. (International Journal of Innovative Research and Scientific Studies, 2026)
Irbid city faces numerous traffic challenges, especially at intersections and traffic circles which are realized as the most problematic areas. This issue could be explained due to continuous development of private vehicle ownership, rapid urbanization and inadequate infrastructure of transportation. The main aim of this study is to discover cost effective and practical solutions for enhancing traffic flow through developing the road networks efficiency, particularly at of the most congested roundabouts in Irbid City. This study integrated MCDM technique, particularly Fuzzy VIKOR and Fuzzy FUCOM, with simulation methodology for the purposes of enhancing traffic flow. The main reason behind employing simulation-based approach is to examine solution efficiency prior to real-world application, in the way that support data-driven decision making. Whereas MCDM is used for solutions ranking based on specific criteria. After that, diverse solutions scenarios were modeled and tested using VISSIM simulation tool. The study results clarified the superiority of the Transit Signal Priority (TSP) scenario over all other suggested solutions, and across all tested volume levels. The results help decision makers to allocate limited budgets more efficiently, through specifying the most efficient enhancement scenarios, and having a better insight regarding performance gains.